Análise comparativa das barreiras de concreto de pontes e viadutos projetadas pelas normas NBR7188:1982 e NBR7188:2013 - Isaia, Horacio João (2022)
In this work, a comparison is made between NBR7188:1982 and NBR7188:2013, referring to the behavior of the structural strength of the concrete barrier determined by its reinforcement, for bridge structures. For the development of this work, two models of New Jersey barrier were used, in which the procedure of analysis and design of these two structural models, is determined through the study of statics and the design to simple bending in rectangular section. In this way, the effect of the force that will act on the concrete barrier of bridges, due to the collision of a runaway vehicle, was considered, taking into account the traffic conditions of the highway in relation to the barrier. Through this calculation methodology, the reinforcement areas obtained by the comparative analysis were determined for the two chosen New Jersey barrier models. The result of the calculations carried out for the analyzes carried out indicated that the change of the NBR7188 code had little influence on the structural strength of the barrier. The increase in reinforcement, approximately equal to that of strength, was only 8.7%. The consequence of the effects of the barrier on the cantilevered slab of the structure that supports it was also considered in this work and analyzed through the comparison between the two reference codes. This consequence resulted in an addition of reinforcement to the cantilever slab. The percentage of reinforcement increase was 217.87%, in the unfavorable position corresponding to the support of the slab. Finally, to give a more comprehensive approach, a comparison was made of the concrete barrier between NBR7188:2013 and another foreign code, choosing the American code AASHTO (2012), and the result showed an adoption of control measures strict compliance with the structural strength of the barrier, by AASHTO (2012), reflecting an increase in reinforcement of 72.3% in relation to the Brazilian code. As NBR7188:2013 does not include changes in the geometry of the barrier element, its functionality related to the safety of the vehicle and its occupants will not be addressed, only the structural aspects of the barrier and the elements connected to it will be addressed.